Multi-hosting UEFA European Football Championship: fair enough between participating teams? - Brocherie, F.; De Larochelambert, Q.; Millet, G. P. (Science and Medicine in Football, 2023)
Purpose: To describe the effects of travel distance and bio-meteorological conditions on the 2020 multi-hosting UEFA European Championship`s match outcomes and progress in competition. Methods: Teams` basecamps, distance from match venues, match outcomes (defeat, draw and win), bio-meteorological data (ambient air temperature, relative humidity and wet bulb globe temperature) and corresponding FIFA world ranking were extracted from the UEFA and FIFA websites; and analyzed through Chi-squared test (impact of basecamp location on match outcomes), Kruskal-Wallis test (distribution of travel distances carried out), ordinal regressions (with match outcomes and competition phases as variables of interest and FIFA ranking and venue distance as explanatory variables) and principal component analysis (with the bio-meteorological conditions and match outcomes for each match). Results: Teams with basecamp near match venue improved their match outcomes. However, neither the Kruskal-Wallis test (p > 0.05) nor ordinal regressions (odds ratio (OR) > 0.96, p > 0.403) identified any significant effect of travel distance on match outcomes. FIFA ranking improved the likelihood of a favorable match outcome (OR = 0.87, p = 0.001) and progression in competition (OR = 0.97, p = 0.003). Despite some matches were played in more stressful bio-meteorological conditions, no associations were found with match outcomes (r = -0.07 to 0.19, p > 0.188). Conclusions: These findings cannot conclusively clarify on the effects of travel and bio-meteorological conditions on match outcomes and progress in the multi-hosting UEFA European championship, but suggest to carefully consider these variables for future multi-hosting competition to avoid any discrepancies between teams.